Elucidating important structural features for the binding affinity of spike ‐ SARS‐CoV‐2 neutralizing antibody complexes. Issue 3 (17th November 2021) - Sharma, Divya; Rawat, Puneet; Janakiraman, Vani; Gromiha, M. Michael
Abstract: The coronavirus disease 2019 (COVID‐19) has affected the lives of millions of people around the world. In an effort to develop therapeutic interventions and control the pandemic, scientists have isolated several neutralizing antibodies against SARS‐CoV‐2 from the vaccinated and convalescent individuals. These antibodies can be explored further to understand SARS‐CoV‐2 specific antigen–antibody interactions and biophysical parameters related to binding affinity, which can be utilized to engineer more potent antibodies for current and emerging SARS‐CoV‐2 variants. In the present study, we have analyzed the interface between spike protein of SARS‐CoV‐2 and neutralizing antibodies in terms of amino acid residue propensity, pair preference, and atomic interaction energy. We observed that Tyr residues containing contacts are highly preferred and energetically favorable at the interface of spike protein–antibody complexes. We have also developed a regression model to relate the experimental binding affinity for antibodies using structural features, which showed a correlation of 0.93. Moreover, several mutations at the spike protein–antibody interface were identified, which may lead to immune escape (epitope residues) and improved affinity (paratope residues) in current/emerging variants. Overall, the work provides insights into spike protein–antibody interactions, structural parameters related to binding affinity and mutational effects on binding affinity change, which can be helpful to develop better therapeutics against COVID‐19.